2000
DOI: 10.1093/protein/13.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of horseradish peroxidase in Saccharomyces cerevisiae and Pichia pastoris

Abstract: The ability to engineer proteins by directed evolution requires functional expression of the target polypeptide in a recombinant host suitable for construction and screening libraries of enzyme variants. Bacteria and yeast are preferred, but eukaryotic proteins often fail to express in active form in these cells. We have attempted to resolve this problem by identifying mutations in the target gene that facilitate its functional expression in a given recombinant host. Here we examined expression of HRP in Sacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
96
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 45 publications
7
96
2
2
Order By: Relevance
“…Some incompatibilities between the expressed gene and heterologous host, such as codon usage or the recognition of signal sequences, can be overcome by changing the gene sequence. Thus, achieving functional expression is a good target for directed evolution (13,42,43).Laccases, like other ligninolytic enzymes, are notoriously difficult to express in nonfungal systems. The laccase from Myceliophthora thermophila (MtL) used in this work was previously expressed only in Aspergillus oryzae (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some incompatibilities between the expressed gene and heterologous host, such as codon usage or the recognition of signal sequences, can be overcome by changing the gene sequence. Thus, achieving functional expression is a good target for directed evolution (13,42,43).Laccases, like other ligninolytic enzymes, are notoriously difficult to express in nonfungal systems. The laccase from Myceliophthora thermophila (MtL) used in this work was previously expressed only in Aspergillus oryzae (6).…”
mentioning
confidence: 99%
“…Some incompatibilities between the expressed gene and heterologous host, such as codon usage or the recognition of signal sequences, can be overcome by changing the gene sequence. Thus, achieving functional expression is a good target for directed evolution (13,42,43).…”
mentioning
confidence: 99%
“…The only reasonable candidate for a bond with the 5-methyl was Leu 37 . This residue has not been assigned any function in the HRP active site, but directed evolution experiments have shown that its mutation into an isoleucine improves enzymatic activity (28). Modeling of a glutamate or an aspartate (an isoleucine steric analog) at this site gave the nearest approach distances of 1.5 and 2.1 Å, respectively (Fig.…”
Section: Structure Superposition and Choice Of Mutations-mpomentioning
confidence: 99%
“…To maintain the glycosylation pattern of the surface-bound HRP, we used the same yeast host for heterologous expression of the soluble enzyme. Because HRP is expressed poorly in this yeast (14,22), we used a strain of , discovered in each round of evolution. Red, yellow, blue, and green bar colors represent substrates 1, 2, 3, and 4, respectively; hatched and solid bars designate surface-bound and soluble HRP, respectively.…”
mentioning
confidence: 99%
“…The L and D letters designate the direction of enantiopreference; the Roman numerals after the letters define the round of directed evolution; the r and/or s letters after the Roman numerals indicate whether these variants were isolated from the random or saturated mutagenesis libraries, respectively. Mutations: LIr (Arg178Gln), LIs (Phe68Leu, Gly69Ala, Asn72Glu, Ser73Leu, Ala74Tyr) (14), LIrs (LIr ϩ LIs), LIIr (LIrs ϩ Gln147Arg), LIII (LIIr ϩ Asn158Asp), DIs (Phe68Glu, Gly69Pro, Asn72Lys) (14), DIIs (DIs ϩ Asn137Arg, Ala140His, Phe142Lys, Phe143Met), and DIII (DIIs ϩ Ser167Ile).…”
mentioning
confidence: 99%